Gender equality under siege: Perceptions and satisfaction of telecommuting women workers with the distribution of unpaid work during the Covid-19 lockdown - Santos, M. H.; Rosa, M.; Correia, R. B.; Xavier, E. (Ex Aequo, 2022)
This study analyses the impact of the Covid-19 pandemic on the division of domestic work as regards women in opposite-gender relationships, telecommuting and living as a couple, during the first lockdown in Portugal. Quantitative and qualitative data was collected (N=171) to understand women's perceptions of time spent on unpaid work, satisfaction, and main difficulties in this period. Results revealed women's dissatisfaction, especially mothers of underage children, who perceived an increase in caregiving tasks. Women's satisfaction also impacted their perception of the causes for these gender asymmetries. The less satisfied women ascribe gender inequalities mainly to socio-normative factors and gender stereotypes, while the more satisfied women ascribe them to aspects of socialisation and upbringing, as well as innate dispositions that differ between men and women. The trend towards more equality found prior to Covid-19 was not found.